Oxidation of Benzyl Alcohol and Carbon Monoxide Using Gold Nanoparticles Supported on MnO2 Nanowire Microspheres. Issue 6 (8th January 2014) - Alhumaimess, Mosaed; Lin, Zhongjie; He, Qian; Lu, Li; Dimitratos, Nickolaos; Dummer, Nicholas F.; Conte, Marco; Taylor, Stuart H.; Bartley, Jonathan K.; Kiely, Christopher J.; Hutchings, Graham J.
Abstract MnO2 was synthesised as a catalyst support material using a hydrothermal method. This involved reacting MnSO4⋅H2O and (NH4)2S2O8 at 120 °C for a range of crystallisation times, which affords control over the morphology and phase composition of the MnO2 formed. Gold was deposited on these supports using sol‐immobilisation, impregnation and deposition precipitation methods, and the resultant materials were used for the oxidation of benzyl alcohol and carbon monoxide. The effect of the support morphology on the dispersion of the gold nanoparticles and the consequent effect on the catalytic performance is described and discussed.